CHOCOLATE FORMULATION AS DRUG DELIVERY SYSTEM FOR PEDIATRICS - Mayank, Sharma; Kumar, Jain Dinesh (Indonesian Journal of Pharmacy, 2012)
Chocolate  is  highly  sophisticated  and  infinitely  a  versatile food that can be combined to create completely different taste and texture  sensations.   The  objective  of  the  present  study  is  to develop  a  palatable  chocolate  formulation  of  Domperidone  and Cetirizine  for  pediatric  administration  and  to  increase  patient’s desire  to  consume  the  medication.  In  present  investigation chocolate  base  is  prepared  by  use  of  cocoa  powder,  coco  butter, lecithin,  and  pharmaceutical  grade  sugar.  Thereafter  drug  is incorporated  to prepared  chocolate base.  The medicated chocolate prepared  is  evaluated  for  appearance,  moisture  content determination using digital Karl Fischer titrator, blooming test, drug content  determination  &  drug  excipient  interaction  by  differential scanning calorimetry.Key words: Medicated Chocolate, Pediatrics, Chocolate formulation